Color image enhancement using filtering and contrast enhancement - Budi Utami Fahnun; Lukman Safri Andani; Hadyan Mardhi Fadlillah; Hendri Dwi Putra (Institute of Computer Science (IOCS), 2023)
Image is an efficient media for information and communication. Filtering on image enhancement is one of the processes in image processing to reduce noise in the image. This study uses the type of noise Salt & Pepper to be applied to flower images and scenic images that the author uses in this study as a comparison test of filtering methods. Filters used in testing and comparison are Median Filter, Mean Filter, and Gaussian Filter. This research also applies the Contrast Enhancement process to highlight certain aspects contained in the image. From the results of testing and comparison of filtering methods it can be concluded that the best method for handling Salt & Pepper noise is Median Filter, which has the best MSE value is 0.7329 to the worst MSE value is 26,766, the best RMSE value is 0.8561 to the worst RMSE value is 5.1736, and the best PSNR value is 49,513 to the worst PSNR value is 33,889 . This research concludes that it has succeeded in making an application of Image Enhancement and comparison Using Median Filter, Mean Filter, Gaussian Filter, And Contrast Enhancement using MATLAB 2016b which can reduce Salt & Pepper noise.